Severe Abdominal HAE Attacks: An Analysis of 7 Cases - Stobiecki, Marcin; Obtulowicz, Piotr; Porebski, Grzegorz; Dyga, Wojciech; Czarnobilska, Ewa; Obtulowicz, Krystyna (Archives of Clinical and Medical Case Reports, 2019)
Abdominal angioedema attacks are a frequent and typical symptom of hereditary angioedema (HAE) but very often generate diagnostic problems. The study presents laboratory and clinical findings of 7 patients with HAE 1/2 hospitalized due to severe attacks. In all cases, at admittance severe abdominal pain, flatulence, strong weakness, different grade of nausea/vomiting or diarrhoea and abundant free fluid in peritoneal cavity were present. In the history of all patients, recurrent 2 to 3 day long abdominal attack with ascites, were announced. Laboratory data done before the treatment showed elevated leukocytosis, hematocrit, serum glucose, high D-dimers and decreased value of APTT. All patients had an abdominal ultrasound examination, in 5 patients additional abdominal angio-CT was performed to exclude thromboembolic episode. The infusion of human C1 inhibitor concentrate was administered as causative treatment. Completely withdrawal of symptoms was noted up to72 hrs after infusion. In addition all laboratory parameters normalized as well as the free fluid in abdominal cavity disappeared, however, D-dimers serum level despite a decreasing tendency reached the normal range just after 2 weeks.